Detection of hazardous vapours in a dusty environment – development of a protective module for chemical sensor using a laboratory setup for systematically simulating realistic conditions. Issue 2 (26th January 2020) - Zuck, Asaf; Sharabi, Hagai; Kendler, Shai
ABSTRACT: The development and testing of a module that removes dust from air based on cyclone technology and its coupling to a chemical detector are described. This development was performed in a laboratory facility that is capable of simulating a harsh environment in which the target material can be mixed with dust at controlled climatic conditions. The size-dependent removal efficiency of the module was tested at different operational conditions. For dust particles of 5 µm and higher, removal efficiency is about 100%. The efficiency for smaller particles is lower, and the overall efficiency is 97%. No significant adverse effect on the detector (flame photometric detector) performance at low to moderate target material concentrations (100 µg/m 3 ), even at high dust concentration, is observed. The cyclone operation does not require the use of consumable and its maintenance is minimal. Power consumption is 15W, which is acceptable for a fixed site or car transportable system and can be further reduced for the handheld version.